Enhanced reactivity and electron efficiency of nanoscale zero-valent iron for nitroaromatic compounds reduction through modification with anthraquinone-2-carboxylic acid - Yuxin Li; Shiqi Yang; Zihan Liu; Yiyang Pan; Pengfei Zhang; Zhiqiu Qu; Chao Shan (Chemical Engineering Journal Advances)
Humic substances (HS) modification favors the reactivity of nanoscale zero-valent iron (nZVI) for water decontamination from nitro-compounds like nitrobenzene (NB), whereas the structural complexity of HS hinders the elucidation of its mechanism. Herein, anthraquinone-2-carboxylic acid (AQC) was employed as a typical model molecule for HS. Through AQC modification, the water contact angle of nZVI evidently increased from 6° to 19°-46°, and the rate constant and electron efficiency for NB reduction under aerobic condition was substantially elevated by 6–10.3 times and 2.5–2.8 times, respectively. Among the AQC-modified nZVI materials with varied molar ratios of AQC/Fe (0.1–3 %), 1 % AQC-nZVI not only exhibited the optimal reactivity and electron efficiency, but also demonstrated enhanced reactivity for various nitroaromatic compounds. Moreover, AQC modification could advance the complete reduction of NB by nZVI to aniline and minimize the accumulation of intermediates. In addition, AQC-nZVI materials could maintain an excellent reduction efficiency over a wide pH range (4–9). Mechanistically, the increase of surface hydrophobicity of nZVI owing to AQC modification promoted the adsorption affinity for NB and redirected more electron transfer to NB. Leveraging both anthraquinone and carboxylic groups, AQC served as electron shuttle to mediate the electron transfer from nZVI to NB whilst accelerating the Fe(II)/Fe(III) circulation. Electrochemical impedance spectroscopy revealed a pronounced decrease in the charge transfer resistance of nZVI from 381.4 Ω to 252.8–337.4 Ω due to AQC modification, thereby facilitating the interfacial electron transfer. This study offers insights into the HS-enhanced reactivity and selectivity of nZVI for water decontamination from nitroaromatic compounds.